Drill Hall or Ball Hall? On Pedagogical Implications of the Old Age Motif in Katherine Mansfield’s Short Story “Her First Ball” - Gładkowska, Eliza; Kwiatkowska, Anna (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2023)
This article uses the short story, “Her First Ball,” by Katherine Mansfield to demonstrate how fiction could be an effective tool in the process of deconstructing and transforming the master narrative of old age among secondary students of English as secondary language (ESL). The story not only offers some language points to focus on and some reading skills to develop, but it also provokes some pertinent questions about the image and meaning of old age. Aging themes in “Her First Ball” could serve as an excellent starting point for discussion among adolescent learners about old age. Moreover, such an open-ended approach to Mansfield’s story could potentially lead to a deepened awareness of the social impact of the semantics of old age as well as the transformation of students’ conceptualization of becoming mature and growing old. In addition, this article is devoted to rebuke such a purely didactic approach by presenting the literary text as a tool for complex pedagogical practices.